2017
DOI: 10.1155/2017/8791406
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Approach to the Biodynamic Modeling of a Human Finger

Abstract: In an effort to understand the vibration-induced injuries incurred by manual workers, mechanical models are developed and used to predict the biodynamic responses of human body parts that are exposed to vibration. Researchers have traditionally focused on the arms and hands, but there has been only limited research on finger modeling. To simulate the accurate response of a single finger, a detailed mechanical model based on biodynamic finger measurements is necessary. However, the development of such models ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The transducer was positioned between the palm and carpal bones near the wrist ( Figure 2 b), allowing the signal to be transmitted from the transducer to each of the five sensors through each finger bone. The transmitted acoustic signal contains anatomical information about the fingers (bone, cartilage, tendon, and muscle tissues) and relies on their geometries as well as their biomaterials and biomechanical properties [ 47 , 48 ]. Principal component analysis (PCA) of the acoustic spectrum of each finger was conducted using MATLAB.…”
Section: Multichannel Bioacoustic Identity Authenticationmentioning
confidence: 99%
“…The transducer was positioned between the palm and carpal bones near the wrist ( Figure 2 b), allowing the signal to be transmitted from the transducer to each of the five sensors through each finger bone. The transmitted acoustic signal contains anatomical information about the fingers (bone, cartilage, tendon, and muscle tissues) and relies on their geometries as well as their biomaterials and biomechanical properties [ 47 , 48 ]. Principal component analysis (PCA) of the acoustic spectrum of each finger was conducted using MATLAB.…”
Section: Multichannel Bioacoustic Identity Authenticationmentioning
confidence: 99%
“…Therefore, the package created a single kinematic chain system controlled through torque or motion inputs of each revolute joint. This was ideal as research has shown that the best way to model the human hand is as a straight chain link between the wrist and fingertips [30]. The model was designed to be controlled through motion inputs to simulate the motion of the human hand model.…”
Section: The Computer Systemmentioning
confidence: 99%
“…3B with detailed explanation in Supporting explanation 4. 54 In general, the stiffness of the spring structure, the design of the contactor structure, and the preload are key parameters affecting the performances. The measured output energy with respect to the stiffness of the spring structure, under a preload of 0.7 N and a driving voltage of 20 Volts at 300 Hz is shown in Fig.…”
Section: Effects Of Mechanical Propertymentioning
confidence: 99%